ART initiation among women newly diagnosed with HIV in a contraceptive trial in sub-Saharan Africa. Issue 4 (3rd April 2022) - Beesham, Ivana; Issema, Rodal; Palanee-Phillips, Thesla; Onono, Maricianah; Evans, Shannon; Beksinska, Mags; Ahmed, Khatija; Kasaro, Margaret P.; Batting, Joanne; Deese, Jennifer; Dlamini, Lunga; Yankurije, Berthe; et al.
ABSTRACT: Current guidelines recommend starting antiretroviral therapy (ART) as soon as possible after HIV diagnosis to reduce morbidity, mortality and onward HIV transmission. We examined factors influencing ART initiation by women who seroconverted during the Evidence for Contraceptive Options and HIV Outcomes (ECHO) Trial. ECHO, conducted between 2015 and 2018, enrolled HIV-negative, sexually active women, aged 16–35 years, from four African countries. Follow-up was 12–18 months, with quarterly HIV testing. Women with incident HIV infection received extensive counselling by trial staff and referral to local facilities for HIV care. Of 304 women with ≥90 days follow-up time since HIV diagnosis, 186(61.2%) initiated ART within 90 days, 69(22.7%) initiated after 90 days, and 49(16.1%) had not initiated by the end of the study. There were no statistically significant differences in characteristics among women who initiated ART ≤90 days versus those who did not. Frequent reasons for delayed or non-initiation of ART included not feeling ready to start ART and being newly diagnosed. In a large clinical trial, ART initiation was modest within 90 days of HIV diagnosis and grew to 84% with longer observation. Despite extensive counselling on the importance of early ART initiation, personal barriers delayed some women from starting ART.